Efektivitas mHealth untuk Meningkatkan Kontrol Glikemik dan Kepatuhan Diabetes Melitus Tipe 2 pada Pasien Dewasa - Hani Andriyana; Meira Erawati; Untung Sujianto (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of Mobile Health (mHealth) in improving glycemic control and adherence in patients with type 2 diabetes mellitus. The method used is a systematic review. The results of this study are mHealth-based health interventions including blood sugar monitoring services with applications, short messages (SMS), voice calls via cell phones, video conferencing, and central call services conducted by health workers in 2-13 month intervals have benefits in increasing glycemic control and adherence in patients with type 2 diabetes mellitus. Services provided by health workers include health education, self-monitoring of blood sugar, diet counseling, healthy lifestyle tips, exercise, face-to-face counseling with health workers, stress management, and foot care. The conclusion of this study is that the mHealth program is effective in improving glycemic control and adherence in type 2 diabetes mellitus patients in addition to diabetes care in general